Phytoremediation with Sunflower (Helionthus annus) and Its Capacity for Cadmium Removal in Contaminated Soils - Ogungbile, Peter Oyelade; Ajibare, Adefemi Olatayo; Enochoghene, Adebisi Esther; Ogunbode, Timothy Oyebamiji; Omotayo, Olumide Ekundayo Omotayo; Ekanade , Christiana Tinuola; Sridhar, Mynepalli Kameswara Chandra; Akande, John Adebayo (Tecno Scientifica Publishing, 2024)
This study assessed the phytoremediation potential of sunflowers for removing cadmium from the soil around a paint manufacturing industry in Eleyele, Ibadan. Background levels of Cd in the topsoil and subsoil were determined. The site was divided into two plots. Organo-mineral fertilizer (OMF) was applied to the first plot, which served as the experimental plot, while the second plot was without OMF and served as the control. Concentrations of cadmium in the plants were determined using an Atomic Absorption Spectrophotometer. Baseline mean Cd contents were 29.23 mg/kg and 33.30 mg/kg for topsoil and subsoil, respectively. Over the planting period, the sunflower plants removed 53.1% and 51.6% of Cd from the topsoil and subsoil in the test plot, while 40.65% and 47.80% were removed from the topsoil and subsoil, respectively, in the control. Cd absorption from the contaminated soils was found to be translocated to all parts of the sunflower. The concentrations of Cd in the sunflower parts were as follows: root system (10.70 mg/kg), shoot (8.17 mg/kg), leaves (6.43 mg/kg), and seeds (2.52 mg/kg) for the test plot. For the control plots, Cd in the root, shoot, leaves, and seeds were 7.60 mg/kg, 7.43 mg/kg, 4.75 mg/kg, and 2.03 mg/kg, respectively. The study confirmed that sunflowers have the potential to remediate Cd from contaminated soil, and this potential was enhanced by the application of OMF.